Developing the effectiveness of professional audit judgment based on the mindfulness of auditors - Alireza Kamalgharibi; Mansour Garkaz; alireza matoufi; Mehdi Safari Gerayli (Iranian Journal of Finance, 2023)
Judgment in the auditing profession as a subjective criterion in the decisions of auditors has a significant role in improving the quality of decision support for analysts, shareholders, and investors in the capital market. Therefore, recognizing the qualitative characteristics in this area can help the theoretical development of improving the quality of auditors' professional judgments. The purpose of this study is to develop the effectiveness of auditing professional judgment based on the mindset of auditors. In this study, to identify the components (auditing professional judgment) and research propositions (themes of auditors' mindfulness), meta-synthesis analysis was used with the participation of 12 experts and experts in the field of accounting and financial management at the university level. In the quantitative part, the identified components and propositions in the form of matrix questionnaires were evaluated by interpretive analysis by 18 auditors with work experience and a level of technical and specialized knowledge. The results showed that the statement of inferential mindfulness is the most influential theme of intuitive judgment in auditing, which can cause auditors to perform more effectively in professional judgment. This result suggests that inferential mindfulness is a factor in intuition in professional judgment.